Practice Analysis for mid-level Pharmacy Workers in South Africa - Boschmans, Shirley-Anne; Fogarty, Teri-Lynne; Schafermeyer, Kenneth W; Mallinson, R. Kevin (Pharmacy Education, 2015)
Background: In South Africa, educational programmes are being developed for new cadres of mid-level pharmacy workers. Therefore, a practice analysis was needed to ensure that these programmes address workplace needs. Aims: To determine and verify, in accordance with published scopes of practice, the responsibilities (i.e., what they will do) and the competencies (i.e., knowledge, abilities, and skills) that pharmacy technicians will need to practice successfully. Methods: The study used the “Job Analysis at the Speed of Reality” (JASR) method in which focus groups of subject matter experts (SMEs) developed categorised lists of job functions. The SMEs represented both pharmacists and mid- level workers from a range of practice sites. Results: A task list for pharmacy technicians was developed from focus group data. Conclusions: Results of the practice analysis provide valuable information for educators, employers, and other stakeholders to ensure that curricular content are practice-related and relevant to all practice settings.